# Limit Examples Here we will look at specific examples using the limit. ### Recall: Suppose $$ \lim_{x\to a}f(x)=L\,\,\text{ and }\,\,\lim_{x\to a}g(x)=M $$ Then 1. ${\displaystyle \lim_{x\to a}\left[f(x)\right]}^{r}{\displaystyle =\left[\lim_{x\to a}f(x)\right]^{r}=L^{r}}$ where $r$ is a positive number. 2. ${\displaystyle \lim_{x\to a}cf(x)=c\lim_{x\to a}f(x)=cL}$ where $c$ is a real number. 3. ${\displaystyle \lim_{x\to a}\left[f(x)\pm g(x)\right]=\lim_{x\to a}f(x)\pm\lim_{x\to a}g(x)=L\pm M}$. 4. ${\displaystyle \lim_{x\to a}\left[f(x)g(x)\right]=\left[\lim_{x\to a}f(x)\right]\left[\lim_{x\to a}g(x)\right]=L\cdot M}$. 5. ${\displaystyle \lim_{x\to a}\frac{f(x)}{g(x)}=\frac{\lim_{x\to a}f(x)}{\lim_{x\to a}g(x)}=\frac{L}{M}}$ where $M\ne0$. 6. ${\displaystyle \lim_{x\to a}x}=a$ 7. ${\displaystyle \lim_{x\to a}b}=b$ 8. ${\displaystyle \lim_{x\to \infty}\frac{1}{x}}=0$ (thm. 5) 9. If $f(x)=g(x)$ for all $x\ne a$, then ${\displaystyle \lim_{x\to a}f(x)=\lim_{x\to a}g(x)}$. (cor. 1) 10. If $\lim_{x\to a^{+}}f(x)\ne\lim_{x\to a^{-}}f(x)$, then we say $\lim_{x\to a}f(x)$ does not exists. (cor. 2) --- #### Example 1 Evaluate the limit: $$ \lim_{x\to3}\dfrac{x^{2}+3x+4}{x^{2}+7} $$ SOLUTION: $$ \begin{align*} \lim_{x\to3}\dfrac{x^{2}+3x+4}{x^{2}+7} & =\dfrac{\lim_{x\to3}x^{2}+\lim_{x\to3}3x+\lim_{x\to3}4}{\lim_{x\to3}x^{2}+\lim_{x\to3}7}\\ & =\dfrac{\left(\lim_{x\to3}x\right)^{2}+3\lim_{x\to3}x+4}{\left(\lim_{x\to3}x\right)^{2}+7}\\ & =\dfrac{\left(3\right)^{2}+3\cdot3+4}{\left(3\right)^{2}+7}\\ & =\frac{11}{8} \end{align*} $$ --- #### Example 2 Evaluate the limit: $$ \lim_{x\to64}\dfrac{\sqrt{x}-8}{x-64} $$ SOLUTION: $$ \begin{align*} \lim_{x\to64}\dfrac{\sqrt{x}-8}{x-64} & =\lim_{x\to64}\dfrac{\sqrt{x}-8}{x-64}\cdot\left(\dfrac{\sqrt{x}+8}{\sqrt{x}+8}\right)\\ & =\lim_{x\to64}\dfrac{x-64}{(x-64)\cdot(\sqrt{x}+8)}\\ & =\lim_{x\to64}\dfrac{1}{\sqrt{x}+8}\\ & =\dfrac{\lim_{x\to64}1}{\lim_{x\to64}\sqrt{x}+\lim_{x\to64}8}\\ & =\dfrac{1}{\sqrt{\lim_{x\to64}x}+8}\\ & =\dfrac{1}{\sqrt{64}+8}\\ & =\dfrac{1}{8+8}\\ & =\dfrac{1}{16} \end{align*} $$ --- #### Example 3 Let $$ f(x)=\begin{cases} x^{2}+1 & x\le1\\ 3x-2 & x>1 \end{cases} $$ Evaluate: 1. $f(1)$ 2. ${\displaystyle \lim_{x\to1}f(x)}$ SOLUTION: 1. Evaluate $f(1)$ means to evaluate $f$ exactly when $x=1$. According to the definition of the piecewise function we have $$ f(1)=1^{2}+1=2. $$ 2. In order to evaluate this piecewise function we must first evaluate $\lim_{x\to1^{-}}f(x)$ and $\lim_{x\to1^{+}}f(x)$. If the two are equal $L$ then we say $\lim_{x\to1}f(x)=L$; however, if the two are not equal we say $\lim_{x\to1}f(x)$ does not exist. $$ \begin{aligned}\lim_{x\to1^{-}}f(x) & =\lim_{x\to1^{-}}\left(x^{2}+1\right)=1^{2}+1=2\\ \lim_{x\to1^{+}}f(x) & =\lim_{x\to1^{+}}\left(3x-2\right)=3(1)-2=1 \end{aligned} $$ Since $\lim_{x\to1^{-}}f(x)\ne\lim_{x\to1^{+}}f(x)$ we say $\lim_{x\to1}f(x)$ does not exist. --- #### Example 4 Evaluate the limit: $$ \lim_{h\to0}\dfrac{\frac{1}{x+h}-\frac{1}{x}}{h} $$ SOLUTION: First, we will simplify $\dfrac{\frac{1}{x+h}-\frac{1}{x}}{h}$ $$ \begin{align*} \dfrac{\frac{1}{x+h}-\frac{1}{x}}{h} & =\dfrac{\left(\frac{x}{x}\right)\cdot\frac{1}{x+h}-\frac{1}{x}\cdot\left(\frac{x+h}{x+h}\right)}{h}\\ & =\dfrac{\frac{x-(x+h)}{x(x+h)}}{h}\\ & =\dfrac{\frac{-h}{x(x+h)}}{h}\\ & =\dfrac{1}{h}\cdot\left(\dfrac{-h}{x(x+h)}\right)\\ & =-\dfrac{1}{x(x+h)} \end{align*} $$ Next, we notice that $\dfrac{\frac{1}{x+h}-\frac{1}{x}}{h}=-\dfrac{1}{x(x+h)}$ for all $h\ne0$. Thus, by Corollary 1 we have $$ \lim_{h\to0}\dfrac{\frac{1}{x+h}-\frac{1}{x}}{h}=\lim_{h\to0}\dfrac{-1}{x(x+h)}=-\dfrac{1}{x(x+0)}=-\dfrac{1}{x^{2}}. $$ --- #### Example 5 Evaluate the limit: $$ \lim_{h\to0}\dfrac{\sqrt{x+h}-\sqrt{x}}{h} $$ SOLUTION: First, we simplify $\dfrac{\sqrt{x+h}-\sqrt{x}}{h}$: $$ \begin{align*} \dfrac{\sqrt{x+h}-\sqrt{x}}{h} & =\dfrac{\sqrt{x+h}-\sqrt{x}}{h}\cdot\left(\dfrac{\sqrt{x+h}+\sqrt{x}}{\sqrt{x+h}+\sqrt{x}}\right)\\ & =\dfrac{(x+h)-(x)}{h\left(\sqrt{x+h}+\sqrt{x}\right)}\\ & =\dfrac{h}{h\left(\sqrt{x+h}+\sqrt{x}\right)}\\ & =\dfrac{1}{\sqrt{x+h}+\sqrt{x}} \end{align*} $$ Next, notice $\dfrac{\sqrt{x+h}-\sqrt{x}}{h}=\dfrac{1}{\sqrt{x+h}+\sqrt{x}}$ for all $h\ne0$. Thus, by Corollary 1 we have $$ \lim_{h\to0}\dfrac{\sqrt{x+h}-\sqrt{x}}{h}=\lim_{h\to0}\dfrac{1}{\sqrt{x+h}+\sqrt{x}}=\dfrac{1}{\sqrt{x+0}+\sqrt{x}}=\dfrac{1}{2\sqrt{x}} $$